2019
DOI: 10.1177/1747954119834118
|View full text |Cite
|
Sign up to set email alerts
|

The socially effective leader: Exploring the relationship between athletic director political skill and coach commitment and job satisfaction

Abstract: Previous sport management research has demonstrated the positive relationship between political skill and personal career outcomes, but research addressing the question of how leader social effectiveness (i.e. political skill) influences the commitment and satisfaction of subordinates is lacking. This study sought to determine if leader (athletic director) political skill influences subordinate (head coach) evaluations of leader effectiveness, in turn influencing subordinate job satisfaction and commitment. Su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 25 publications
0
10
0
Order By: Relevance
“…Head coach political skill has also been shown to increase subordinates' perceptions of their reputation and leadership effectiveness (Kim et al, 2016). Further, in a study of interscholastic athletic administrators, leader (AD) political skill enhanced subordinates' levels of commitment and job satisfaction (Robinson et al, 2018). Overall, the prevailing data on political skill in sports points to a positive relationship between political skill and career success for coaches.…”
Section: How Political Skill Benefits Sport Professionalsmentioning
confidence: 95%
“…Head coach political skill has also been shown to increase subordinates' perceptions of their reputation and leadership effectiveness (Kim et al, 2016). Further, in a study of interscholastic athletic administrators, leader (AD) political skill enhanced subordinates' levels of commitment and job satisfaction (Robinson et al, 2018). Overall, the prevailing data on political skill in sports points to a positive relationship between political skill and career success for coaches.…”
Section: How Political Skill Benefits Sport Professionalsmentioning
confidence: 95%
“…13 As well, leader self-rated political skill has been shown to positively influence follower attitudes, job satisfaction, and commitment when mediated by leader effectiveness. 19…”
Section: Research Hypotheses Developmentmentioning
confidence: 99%
“…Thus, to improve how servant leadership functions in the context of sport, examining the role of political skill as a potential moderator of the relationship between servant leadership and key organizational outcomes (e.g., leadership effectiveness, commitment and satisfaction) represents a worthwhile contribution to the study and practice of leadership in sport. 19…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Job satisfaction is defined as a happy emotional state or positive emotions that come from assessing one's work or work experience (Brayfield & Rothe, 1951). Furthermore, it is also suggested that job satisfaction is a person's reaction to work or organization (Robinson, Magnusen, & Kim, 2019;Saleem, 2015;Arilaha, Fahri, Nurlela, Jabid, & Buamonabot, 2020). A satisfied employee can encourage a positive attitude by prioritizing organizational interests rather than personal ones (Heriyadi, Tjahjono, & Rahayu, 2020).…”
Section: Introductionmentioning
confidence: 99%